Teacher's Strategy In Improving Reading And Writing Skills Of Second-Grade Students At SDN 100020 Simardoa Padang Lawas Utara Regency - Parulian Siregar; Rahmi Seri Hanida; Rumiah Siregar (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This research aims at describing the teacher's strategy for improving second-grade students' reading and writing skills at SD Negeri 100020 Simardona, Padang Lawas Utara Regency. It is descriptive qualitative research, with data collected through interviews, observations, and documentation. The followings are the findings of this research; a). the teacher's strategy to improve the second graders' reading and writing skills at  SD Negeri Simardona is to read alternately at the beginning of the lesson, read together (joint reading), read in front of the class, read word for word in sequence, and read their own and their classmates' writings in notebooks and on the blackboard, b). strategies for improving writing skills are by copying writing into a notebook, writing on the blackboard, writing dictation, copying writing from textbooks, and giving writing assignments at home.